2017
DOI: 10.1016/j.ophtha.2017.03.044
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy of Spectralis SD OCT Automated Macular Layers Segmentation to Discriminate Normal from Early Glaucomatous Eyes

Abstract: Macular RNFL, mGCL-IPL, and mGCC measurements showed a high diagnostic capability to discriminate between healthy and EG participants. However, macular intraretinal measurements still have not overcome standard pRNFL parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
70
3
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(84 citation statements)
references
References 35 publications
9
70
3
2
Order By: Relevance
“…Retinal thickness is related to a variety of other conditions. For example, reduced thickness of the retinal ganglion cell complex (GCC; a composite retinal layer comprising the retinal layers containing the ganglion cell dendritic synapses with bipolar and amacrine cells, the ganglion cell bodies, and the ganglion cell axons viz., the IPL, GCL, and NFL respectively) has also been associated with a variety of ocular diseases in their early stages, such as glaucoma [56], retinal vessel loss in open-angle glaucoma [57], and chiasmal compression [58]. Similar changes have also been reported in early age-related macular degeneration [59].…”
Section: Discussionmentioning
confidence: 64%
“…Retinal thickness is related to a variety of other conditions. For example, reduced thickness of the retinal ganglion cell complex (GCC; a composite retinal layer comprising the retinal layers containing the ganglion cell dendritic synapses with bipolar and amacrine cells, the ganglion cell bodies, and the ganglion cell axons viz., the IPL, GCL, and NFL respectively) has also been associated with a variety of ocular diseases in their early stages, such as glaucoma [56], retinal vessel loss in open-angle glaucoma [57], and chiasmal compression [58]. Similar changes have also been reported in early age-related macular degeneration [59].…”
Section: Discussionmentioning
confidence: 64%
“…The recent introduction of Spectralis SD-OCT software designed for the analysis of segmented inner macular layers has rekindled interest in the management of glaucoma in adult patients. Recent studies have shown a good diagnostic capacity of inner macular layer segmentation analysis to differentiate between normal eyes and glaucomatous eyes, comparable to that of cpRNFL thickness, in adults [8].…”
Section: Discussionmentioning
confidence: 94%
“…observed in adults that AUCs for overall mRNFL and GCL thicknesses (0.915 and 0.914) tended to be greater than that for cpRNFL global thickness (0.878), and that the AUC for overall IPL thickness was lower. More recently, a similar study using the same new segmentation Software [8] found that the three best parameters were the temporal-inferior sector of pRNFL (AUC, 0.956), the outer inferior sector of mRNFL (AUC, 0.906), the outer-inferior sector of macular inner retinal layer (AUC, 0.876), the the inner-temporal of mGCL (AUC, 0.858) and the inner-temporal of IPL (AUC, 0.854). This study showed that pRNFL still performed better than the other retinal macular layers assessed separately.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 Conversely, some authors did not find any difference between the yield of RNFL and GCC capability to differentiate normal and glaucomatous eyes. 19,20 Nevertheless, VMIAs are a confounding factor for the conclusions that may be drawn from GCC. 21 Therefore, we prompted this study to evaluate the prevalence and potential associations of VMIAs with glaucoma in an elderly population.…”
mentioning
confidence: 99%